COMPREHENSIVE ASSESSMENT OF TREATMENT SATISFACTION WITH COMPLETE DENTURES ARTICULATED WITH THE T-SCAN SYSTEM AND ARTICULATION PAPER - Tanya Bozhkova; Nina Musurlieva (Peytchinski Publishing, 2024)
Background: Prosthetic treatment in case of complete edentulism has the task of restoring the lost chewing function, speech and breathing and preventing the appearance or deepening of the reduction changes of both the soft tissues and the bones in the maxillofacial region, as well as restoring the aesthetic appearance and improving the psyche of the patient The aim of the present pilot study is to evaluate the satisfaction with treatment with complete dentures articulated with articulation paper and the T-SCAN system, which will serve as the basis for a large-scale cross-sectional study. Material and methods: The study includes a sample of 20 completely edentulous patients. The sample consisted of 10 women and 10 men. The studied patients were randomly divided into two groups of 10 people each. The patients were interviewed post treatment [at 5 weeks], a validated questionnaire about oral health-related quality of life in edentulous people [OHIP-EDENT] was applied. Results: The digital occlusal analysis provides more accurate information on the articulation of the prostheses, as it indicates the teeth with increased force in percentages and also the sequence of occurrence of the occlusal contacts. Analysis of occlusal contacts is subjective, and articulating them with this method carries error risks.When using the T-Scan system, patients are more satisfied than the treatment with total patients, as they feel the prostheses are much more comfortable and in much fewer visits. Conclusion: This quantitative methodology can be used as the method of choice for control of occluso-articulation relationships in treatment with total dentures in any dental practice, if technically possible.